Recent advances in cochlear implants. - Zwolan TA (Contemporary Issues in Communication Science & Disorders)
Over the years, numerous technological advances have taken place in regard to the internal and external components of cochlear implant systems. Such advances include improvements in receiver and electrode design and placement, improvements in external component technology that have brought about downsizing and increased efficiency of externally worn speech processors, and improvements in surgical techniques that have resulted in decreased damage to the cochlea following electrode insertion. These advances have resulted in changes in candidacy criteria over time and improved outcomes for adults and children who receive cochlear implants. This article will provide a brief overview of some of the changes and technological advances that have taken place in the field of cochlear implants since they were first introduced.